Soap bubbles in analytical chemistry. Conductometric determination of sub-parts per million levels of sulfur dioxide with a soap bubble - Tinakorn Kanyanee (2018)
Soap bubbles provide a fascinating tool that is little used analytically. With a very low liquid volume to surface area ratio, a soap bubble can potentially provide a very useful interface for preconcentration where mass transfer to an interfacial surface is important Here we use an automated system to create bubbles of uniform size and film thickness. We utilize purified Triton-X 100, a nonionic surfactant, to make soap bubbles. We use such bubbles as a gas-sampling interface. Incorporating hydrogen peroxide into the bubble provides a system where electrical conductance increases as the bubble is exposed to low concentrations of sulfur dioxide gas. We theoretically derive the conductance of a hollow conducting spherical thin film with spherical cap electrodes. We measure the film thickness by incorporating a dye in the bubble making solution and laser transmission photometry and find that it agrees well with the geometrically computed thickness. With the conductance of the bubble-making soap solution being measured by conventional methods, we show that the measured values of the bubble conductance with known bubble and electrode dimensions closely correspond to the theoretically computed value. Finally, we demonstrate that sub-ppm levels of SO2 can readily be detected by the conductivity change of a hydrogen peroxide-doped soap bubble, measured in situ, when the gas flows around the bubble. © 2006 American Chemical Society.